Analisis kemampuan literasi numerasi ditinjau dari keterampilan metakognisi siswa SMA - Gozali, Imam; Nindiasari, Hepsi; Fatah, Abdul (Universitas Sultan Ageng Tirtayasa, 2024)
AbstractThis study aims to analyze the ability of numeracy literacy in terms of metacognition skills of high school students. This type of research is descriptive qualitative research. The research subjects were 33 students of class XI IPA 1 SMAN 21 Tangerang Regency. The subjects that will be studied are 3 students with numeracy literacy abilities who have different metacognitive skills, namely the high category, medium category, and low category. Data collection techniques used were written tests and task-based interviews. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The validity of the data used triangulation techniques to check the test result data with interview data. There are 3 stages in the numeracy literacy ability of students who have metacognitive skills such as the planning stage, monitoring stage, and evaluation stage. The results of the study concluded that: (1) Students who have numeracy literacy skills in terms of metacognitive skills with high categories are able to fulfill the planning, monitoring and evaluation stages properly and correctly (2) the numeracy literacy abilities of students who have metacognitive skills in the medium category have able to meet the planning, monitoring, and evaluation stages even though they are not optimal, and (3) the numeracy literacy skills of students who have metacognitive skills in the low category are only able to fulfill the planning stage, while the monitoring and evaluation stages have not been able to fulfill optimally.